Evaluasi Implementasi Sistem Informasi Keuangan terhadap Efisiensi Proses Akuntansi Pada UMKM Regisha - Lanny Regina Susanti; Ananda Dwi Kurniawan; Lathifah Aisha Nurwanti; Aditya Yoga Pratama; Afif Maulana; Fitri Komariyah (Universitas 45 Surabaya, 2025)
The purpose of this study is to understand results of implementing the financial information system “FIS”; to improve efficiency of accounting processes at MSMEs Regisha Sidoarjo. The kind of research needed is qualitative description through the case study method. This observation indicates that these MSMEs are not recording and managing financial information properly. This happens because the owners cannot afford to pay professional financial managers, and if you use financial software, you have to pay for the software monthly. Implementing “Odoo RP” software can help these MSMEs improve the efficiency, accuracy and quality of their financial reporting